Polygamy and Women's Rights: An Examination of Divorce Litigation in Sharia Court Rulings Pertaining to Revisions in Indonesian Matrimonial Legislation - Analiansyah, Analiansyah; Dhiaurrahmah, Dhiaurrahmah; Jamhuri, Jamhuri; Salam, Abdul Jalil; Iskandar, Mizaj (AL-ISTINBATH : Jurnal Hukum Islam, 2024)
This study aims to assess and elucidate the influence of polygamy on domestic violence as reflected in the Sharia Court rulings in Aceh, as well as the viability of polygamy as a justification for granting divorce petitions. The study of this topic is significant since Islam essentially allows polygamy, provided that men can behave justly. The divorce ruling at the Sharia Court in Aceh revealed that polygamy led to the neglect of women and other forms of domestic violence. Unfortunately, Indonesian laws and regulations do not acknowledge polygamy as a valid ground for women to petition for divorce. The study is normative juridical review in nature. The data source is a judicial ruling. The data is examined under a women's protection framework. The findings indicate that the wife initiated divorce proceedings against her husband for practicing polygamy, which contravened Indonesian marital law and the Compilation of the Islamic Law, namely polygamy conducted without the wife's consent. Furthermore, polygamy often leads to domestic abuse against the wife. Polygamy can be categorized as irresponsible when practiced by a husband lacking steady economic resources, resulting in the neglect of women and their children. This polygamy is likewise deemed a contravention of the rules of marriage in the Islamic jurisprudence. At the present time, polygamy is not recognized as the reason for divorce in the Indonesian law. This study advocates for the inclusion of polygamy without consent as a legal ground for divorce, as the current legislation recognizes only physical domestic violence as a valid justification for divorce.